2022
DOI: 10.1016/j.ymthe.2022.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo and in vivo suppression of SARS-CoV-2 with combinatorial AAV/RNAi expression vectors

Abstract: Despite rapid development and deployment of vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), clinically relevant modalities to curb the pandemic by directly attacking the virus on a genetic level remain highly desirable and are urgently needed. Here we comprehensively illustrate the capacity of adeno-associated virus (AAV) vectors co-expressing a cocktail of three short hairpin RNAs (shRNAs; RNAi triggers) directed against the SARS-CoV-2 RdRp and N genes as versatile and effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…Other studies have engineered colonic organoids to assess the association of hypertension and SARS-CoV-2 infections since hypertension is one of the most common comorbidities in COVID-19 patients ( Li et al, 2020a ). Human intestinal organoids infected with SARS-CoV-2 were used as a model to study infection in the gut ( Wang et al, 2022 ; Zhou et al, 2020b ), which demonstrated that the gut is also another target organ since ACE2 is highly expressed on enterocytes ( Becker et al, 2022 ; Lamers et al, 2020 ). These discoveries could be an explanation to the common gastrointestinal symptoms observed in COVID-19 patients such as diarrhea ( Ye et al, 2020 ).…”
Section: In Vitro Tissue Models and Technologies For Covid-1...mentioning
confidence: 99%
“…Other studies have engineered colonic organoids to assess the association of hypertension and SARS-CoV-2 infections since hypertension is one of the most common comorbidities in COVID-19 patients ( Li et al, 2020a ). Human intestinal organoids infected with SARS-CoV-2 were used as a model to study infection in the gut ( Wang et al, 2022 ; Zhou et al, 2020b ), which demonstrated that the gut is also another target organ since ACE2 is highly expressed on enterocytes ( Becker et al, 2022 ; Lamers et al, 2020 ). These discoveries could be an explanation to the common gastrointestinal symptoms observed in COVID-19 patients such as diarrhea ( Ye et al, 2020 ).…”
Section: In Vitro Tissue Models and Technologies For Covid-1...mentioning
confidence: 99%
“…They have also begun to define the transduction pattern in organoids comprised of heterogeneous cell populations (vector tropism) and the expression profile and localization of transgene product (thereby testing the true selectivity of various “cell-specific” promoters), and they have explored some of the mechanisms of cell attachment of AAV vectors to different cell types within these human tissues. These studies have also used organoids to validate animal study outcomes in an all-human setting and to test novel approaches to gene delivery/editing to target infectious agents such as HIV and COVID-19 ( 132 , 139 ). By using iPSCs, either derived from patients or engineered via CRISPR/Cas9 gene editing, to fabricate these organoids, investigators have provided critical proof-of-concept for the value of using organoids to model a specific disease, e.g.…”
Section: Current Application Of 3d Organoids and Mps Platforms To Stu...mentioning
confidence: 99%
“…First, only one single-sequence siRNA molecule was used. Considering how fast SARS-CoV-2 escape mutations are observed when treated with shRNA [ 44 ], it seems likely that drug resistant RSV variants emerged under therapy. Therefore, in upcoming anti-viral siRNA trials, a mixture of siRNA sequences should be delivered in parallel [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…But the question is: Can escape mutations arise also for these highly conserved regions, or would the virus lose viability or other critical characteristics if this region were to mutate? A recent study shows how fast escape mutations arise upon AAV-mediated shRNA transduction [ 44 ]. Therefore, there is still work to do for us.…”
Section: Introductionmentioning
confidence: 99%